Tubal ectopic pregnancy six years after supracervical hysterectomy. A case report - Asencio Aguedo, Angélica Yeyli (2020)
Ectopic pregnancy in hysterectomized patients is an uncommon event and it is rarely considered in the differential diagnosis. We present the case of a 30-year-old patient with hysterectomy performed 6 years before who presented to the emergency service with a 3-day evolution of lower abdominal pain. Ultrasonography showed a gestational sac with embryo and the presence of free fluid in the Douglas sac. Histological examination of the surgical piece revealed chorionic villi and an embryo within the uterine tube.